Keterkaitan Online Customer Rating, Live Streaming dan Brand Experience Terhadap Keputusan Pembelian Skintific - Diniah, Zahrotu; Setiawan, Fery; Ayuningtyas, Eka Destriyanto Pristi (Widya Manajemen, 2025)
This study is useful for exploring the impact of online consumer reviews, live streaming, and brand experience on the shopping accuracy of Skintific products on Shopee commerce, segmented. The background of the study is the high consumer interest in online skincare products and the utilization of digital features that have not yet been fully understood in terms of their effectiveness in driving shopping accuracy. This study employs a quantitative strategy through accidental sampling method on 112 respondents who have purchased Skintific products on Shopee. The evidence presentation is conducted using increasing linear regression supported by SPSS. The findings of the study show that all three variables significantly impact the purchasing decision, with brand experience being the dominant variable. This study suggests that business actors maximize digital features to build a strong brand experience. The limitations of this research include the scope of objects and the limited number of variables. Further research is recommended to explore other variables such as price, promotion, or the influence of influencers. .